PENGARUH MODEL EXPERIENTAL LEARNING TERHADAP KETERAMPILAN MENULIS NARASI DAN KEMAMPUAN BERBICARA SISWA KELAS V GUGUS 2 KECAMATAN BONTOTIRO KABUPATEN BULUKUMBA - Syaeful Padya; Sulfasyah; Tarman A.Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of implementing Experiential Learning in improving the narrative writing and speaking skills of fifth-grade students in Cluster 2, Bontotiro District, Bulukumba Regency. The research problem focuses on whether the Experiential Learning model can significantly enhance students' narrative writing and speaking skills compared to conventional teaching methods. The research method employed is a quasi-experimental design with a pretest-posttest approach involving two groups: an experimental group using the Experiential Learning model and a control group employing conventional teaching methods. Data were collected through narrative writing and speaking skill tests as well as observations. The population and sample of this study comprised fifth-grade students in Cluster 2, Bontotiro District, Bulukumba Regency. The sample was selected using purposive sampling, involving one class as the experimental group and another as the control group. The results revealed that the implementation of the Experiential Learning model significantly improved the narrative writing and speaking skills of students in the experimental group compared to the control group. This improvement occurred because students in the experimental group experienced a more active, reflective, and collaborative learning process, enabling them to produce more cohesive and structured written and spoken narratives.Conclusion, Experiential Learning has proven effective in enhancing students' narrative writing and speaking skills compared to conventional teaching methods.